THE INFLUENCE OF FOMO AND VISUAL MERCHANDISING ON KKV PRODUCTS PURCHASE DECISIONS AMONG STUDENT IN MANADO CITY - Soewarno, Michael Endrico; Pandowo, Merinda H. C.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to test the influence of fear of missing out (FOMO) and visual merchandising towards purchase decision partially and simultaneously, data were collected through a questionnaire method with a population of 2423 and by using the slovin formula, 96.03 (97) samples were obtained.  However, in this study the sample to be taken was rounded up to 100. The result indicates that both Fear of Missing Out (FOMO) and Visual Merchandising play crucial roles in influencing purchase decisions. When analyzed together (simultaneously), these factors have a combined effect that significantly impacts how consumers decide to buy products. Separately (partially), each factor also shows a distinct influence on purchase decisions. FOMO drives consumers to make purchases out of a fear of missing out on trends or exclusive offers, compelling them to act quickly. Meanwhile, Visual Merchandising enhances the attractiveness and appeal of products through strategic presentation, drawing in consumers and encouraging purchases. The combined and individual impacts of these factors underscore their importance in shaping consumer behavior and driving sales.   Keyword: Fear of Missing Out (FOMO), Visual Merchandising, Purchase Decision